Effect of inquiry science learning on students’ metacognitive skill - Lelasari, Tarsiana; Yohanita, Aksamina Maria; Damopolii, Insar (Journal of Research in Instructional, 2021)
This study aims to determine the effect of the inquiry learning model on the metacognitive skills of class XI science students at SMA Negeri 1 Manokwari. This study used a quasi-experimental approach with a non-equivalent control group. This study took samples of two groups, namely the XI MIA 4 group as the experimental group, and the XI MIA 7 group as the control group. Purposive sampling is used in the sample method. The instrument used is a test consisting of 12 questions in the form of a description. The findings show that the average final metacognitive ability of the experimental group is 61.22, while the average of the control group is 46.69. The data analyst used the Mann-Whitney non-parametric test to determine whether there was a difference in metacognitive ability between students using the inquiry model and students using the conventional model. P= 0.012 < 0.05 indicates that there are differences in metacognitive skills between students who use the inquiry model and students who use the conventional model.